2019
DOI: 10.1155/2019/1945450
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Multiple Sources of Soil Gas in the Tangshan Fault Zone, North China

Abstract: The sources of soil gases in the Tangshan fault zone, North China, were discussed, based on the soil gas compositions and isotopic ratios obtained by measurement in the field and sample analysis in the laboratory. Soil gas compositions and isotopic ratios indicate that air (A) end-member, limestone (L) end-member, and sediment (S) end-member are the major end-member components contributing to the soil gas in our study area, with fractional contributions in the range of 2-15 vol.%, 23-36 vol.%, and 62-65 vol.%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
1
4
0
2
Order By: Relevance
“…In the petroliferous basins considered herein, the leakage of CH 4 and CO 2 will be larger when an earthquake occurs than during normal times (Cui Y et al, 2017). In the active fault of the basin's edge, the leakage of CH 4 and CO 2 is consistent with the intensity of regional tectonic activity (Chen Z et al, 2019a, b).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In the petroliferous basins considered herein, the leakage of CH 4 and CO 2 will be larger when an earthquake occurs than during normal times (Cui Y et al, 2017). In the active fault of the basin's edge, the leakage of CH 4 and CO 2 is consistent with the intensity of regional tectonic activity (Chen Z et al, 2019a, b).…”
Section: Resultssupporting
confidence: 58%
“…They also suggested that the warming effect might be related to seismogenic mechanisms; however, this is relevant only if the geological conditions and basin topography allow the gases to gather, which results in the gases being released to form a CTIB anomaly. Besides, with the absence of greenhouse gases escaping in the Junggar basin's faults and the west Sichuan basin (Cui Y et al, 2017; Chen Z et al, 2019a, b), fewer gases are escaping before EQs in other basins if these basins are without gas reservoirs.…”
Section: Resultsmentioning
confidence: 99%
“…活动断裂带气体地球化学特征常与区域内地震活动密切相关 [68][69][70][71] . 断裂带土壤气体(CO 2 、 CH 4 、Rn 和 Hg 等)在地震前后经常出现特殊的异常现象 [19,72] ,其异常幅度也常随着地震活动的 变化而变化 [42,73,74] .意大利 L'Aquila 地区 6.…”
Section: 气体地球化学异常unclassified
“…It is closely related to the seismogenic process and the occurrence of earthquakes. Earthquakes are caused by a tectonic evolution accompanied by the exchange of matter and energy deep inside the Earth [1][2][3][4], which is mainly transmitted via the release of fluid through active faults and fractures at different depths [5] because faults and fractures are preferential migration pathways for gases (e.g., CO 2 and radon (Rn)) in the deep crust to migrate upward to the surface owing to their enhanced permeability and porosity relative to the surrounding rocks [6][7][8]. Active faults can provide pathways for gas leaks from the solid Earth because they usually increase the permeability of soils [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 is the second most abundant magmatic gas after H 2 O and is the main gas investigated during diffuse degassing studies as well as at many permanent stations using the accumulation chamber method (ACM) [34,35]. Soil gas anomalies are usually complex because they are subject to multiple influences (atmospheric, biogenic, organic, and from the deep crust and mantle [23,25,36,37]) and occasionally, their relationships with seismic events can be ambiguous [4,7,38,39]. Accordingly, if soil gas observations in fault zones become a useful method of fault activity assessment and seismic forecasting, further analysis of their relationships is required and the source identification of soil gas in the seismically active areas is a prerequisite.…”
Section: Introductionmentioning
confidence: 99%